2022
DOI: 10.30682/nm2203f
|View full text |Cite
|
Sign up to set email alerts
|

Table Olive Farmers’ Sources of Risk and Risk Management Strategies

Abstract: Like in all Mediterranean countries, Table olive farming has an important tradition and production potential in western Turkey, and thus it is critical to assess the risk sources and risk management strategies that farmers perceive. This study identifies perceptions of risk sources and managements strategies in the region, clarifying their relative importance, as farmers perceive them, using a survey conducted among 121 selected purposefully farmers. Sociodemographics of farmers and households were identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 51 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…Government should increase the premium subsidy, which is currently 50% to enhance the insurance purchase among farmers. Similarly, Tok (2022) recommended to increase the insurance premium subsidy to 67%. Torkamani (2002), Sherrick et al (2004), Aidoo et al (2014), Ghazanfar et al (2015), Kiran and Umesh (2015), Yakubu et al (2016), Enjolras et al (2012), FAO (2005), Shi (2008), McCarthy (2003), Smith and Baquet (1996) and Makki and Somwaru (2001), respectively.…”
Section: Wtp For Agricultural Insurance and The Link Between Premium ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Government should increase the premium subsidy, which is currently 50% to enhance the insurance purchase among farmers. Similarly, Tok (2022) recommended to increase the insurance premium subsidy to 67%. Torkamani (2002), Sherrick et al (2004), Aidoo et al (2014), Ghazanfar et al (2015), Kiran and Umesh (2015), Yakubu et al (2016), Enjolras et al (2012), FAO (2005), Shi (2008), McCarthy (2003), Smith and Baquet (1996) and Makki and Somwaru (2001), respectively.…”
Section: Wtp For Agricultural Insurance and The Link Between Premium ...mentioning
confidence: 99%
“…Insurance is one of the most effective risk management strategies to prevent negative outcomes of potential risks and uncertainties. Tok (2022) suggested that insurance against financial losses was one of the most important risk management strategy among farmers. Agricultural insurance aims to reduce the income instability in the agricultural sector and minimize the adverse effects of natural disasters such as droughts, hail etc.…”
Section: Introductionmentioning
confidence: 99%